Young women's site-specific fear of crime within urban public spaces in Seoul. Issue 3 (4th May 2022) - Min, Young Hee; Byun, Gidong; Ha, Mikyoung
ABSTRACT: Many studies revealed that vegetation in parks evokes fear of crime for women in a certain environmental context, and it significantly inhibits the restorative qualities of urban green spaces. A quasi-experimental on-site study was conducted at two privately owned public spaces in a central business district of Seoul, to investigate what aspects of sites trigger women's fear of crime and why. Female participants visited two contrasting sites (N = 30) – one with dense trees and one with an open lawn – at both day and night and indicated perceived fear intensity on interactive maps with four levels (0–3). In total, 540 overlaid grid cells were encoded using the presence of physical attributes, such as vegetation, street furniture, lighting, security camera, artwork, borders of buildings, and roads. A generalized linear model estimated the effects of the physical attributes to determine whether they were positively or negatively associated with assessed fear intensity. Insufficient lighting and absence of people after working hours at the wooded site induced a large increase in perceived fear intensity from daytime. In geographically mapping fear of crime, participants showed the highest level of fear for violence and sex crimes in the alley enclosed with woods. GRAPHICAL ABSTRACT: uf0001